Assessment of Social Vulnerability in Argentina Using GIS. Development of a Local Index - Natacha Soledad Represa (Anuário do Instituto de Geociências, 2018)
Social vulnerability assessment is a central part of mitigation and adaptation to risks. Social vulnerability maps can be used to improve land use management and economic development. This paper presents a methodological proposal for elaborating a social vulnerability index at local level, using the statistical technique of principal component analysis in a geographic information system. As an advantage, this technique facilitates the weighting of indicators by decreasing the subjectivity of the process. The Argentine Republic was analyzed as an application case. Based on the variables included in the national census, 19 descriptive indicators were constructed, which were summarized in a single index that allowed the entire territory to be categorized at the level of census radio. The classification used was useful in discriminating against census stations with extreme conditions of social vulnerability. With some exceptions, greater social vulnerability was observed in the western and northern sectors of the country. In contrast, the Pampean and Patagonian region and the capital city of the country had the lowest rates.